The Round Temple on the Tiber and the Restoration of Ancient Sanctuaries under Augustus - Lipps, Johannes (Archäologischer Anzeiger, 2014)
Since the study published in 1973 by Friedrich Rakob and Wolf Dieter Heilmeyer, a restoration phase of the Round Temple on the Tiber has been dated to the Tiberianperiod – on account of stylistic analysis of its capitals – and has been interpreted as a response to the flooding of the Tiber in 15 A.D. On the basis of more recent analyses, however, this study shows that the supposedly firmly dated specimens to which the capitals were compared and which were adduced as evidence of a Tiberian dating in fact have to be assigned to the Augustan period. Consequently, the repairs to the Round Temple on the Tiber may well have been carried out in the Augustan period, too. This places the edifice in a new historical context. The repairs observed here have to be reclassified as part of the Augustan efforts, attested in literature, to restore the sacred architecture of Rome’s past.